Research on Steer-by-Wire System in Electric Vehicle - Zhang Yonghui; Chen Dingyue; Yu jiayu; Wang Yue; Chen Lihao; Chen junyu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexSteer-by-wire (SBW) system in electric vehicle replaces the mechanical connection between steering wheel and front wheels with cable in the traditional steering system, which overcomes the limitations of the traditional steering system for the drivers. It is a hot research topic in the field of new energy vehicles in the future. The proposed new structure of SBW in electric vehicle is introduced; its integrated control strategy consists of three modules. A coordinated control determines the body forces/moment required to achieve electric vehicle motion objectives. The body forces/moment are allocated to braking and steering subsystems based on phase plane notion. The coordination of these actuators is achieved through the controller of the feedback gains with respect to electric vehicle speed. The gain scheduled steering controller provides the desired yaw rate damping while keeping the yaw-lateral motion decoupled. The simulation test results show the effectiveness of the proposed architecture and steering control system when the SBW in electric vehicle is subject to critical driving situations. Our work provided a reference for further research of SBW system.